Employee empowerment and job satisfaction: an empirical study of Malaysian management - al-Kahtani, Ali Hussain; Sulaiman, Mohamed; Shariff, Suriati; Abu Jarad, Ismael (IDOSI Publication, 2011)
Previous research in the Human Resource Management showed that job satisfaction has been explained by different variables including the working environment, organizational policies and job characteristics. However, little attention has been given to employee empowerment as a predictor of employee satisfaction. This study focuses on employee empowerment and employee job satisfaction as an indicator to the leadership effectiveness of Malaysian managers.